Nursing students satisfaction in clinical learning environment Al-Makassed training hospital in Palestine - Shqirat, Jamil M.A.; Mohammad Saleem Faraj, Saleem; Sedek, Muliati; Omar, Siti Rohana; Ariffin, Hafzan; Che Amran, Aliza (Zhongguo Hangtian Gongye Zonggongsi, 2024)
This study aims to determine the satisfaction of nursing students’ in clinical learning environment (CLE) at Al-Makassed hospital. The study also focuses in investigating the respondents’ background in terms gender, place of residence and years of study towards their satisfactions in clinical learning environment. The research questions related to the nursing students’ satisfaction includes cooperation of the patients, hospital policy, nursing clinical instructors, clinical practice, crew relationship and practical implementation to theoretical learning. Data are collected from 120 nursing students in Al-makassed hospital in Palestine, and the items of the questionnaire are developed according to the research questions.The data is analyzed using statistical packages of social science (SPSS) program and the results reveal that nursing students are satisfied with the clinical learning environment satisfaction (CLE) in AL-Makassed Hospital.However, the result reveals that nursing students’ satisfaction are not affected by the respondents’ demographic data; in relation to gender, place of residence and years of study. Also, the study indicates that nursing student satisfaction in the close units were more than the open units in relation to the clinical environment.